1991
DOI: 10.1002/ajpa.1330850107
|View full text |Cite
|
Sign up to set email alerts
|

Blood genetic systems in four Amazonian tribes

Abstract: Data on 31 genetic systems were obtained for 421 individuals belonging to the Arara, Araweté, Mundurucu, and Jamamadi tribes of northern Brazil. The Jamamadi depart farthest, and the Mundurucu least, from South American Indian averages. These data are analyzed together with those of 24 other Amazonian groups. Genetic distances and corresponding dendrograms indicate a cluster of 14 related tribes living north of the Amazon river. These genetic results show only a modest correlation with linguistic and geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
(3 reference statements)
2
9
0
Order By: Relevance
“…One individual was GM 1,17 13, a common phenotype of the Mongoloid race. The distribution of KM allotypes was similar to other South American Indian tribes (Salzano et al , 1991; J. P. Pandey and E L. Black, unpublished observations), with the exception of Huaorani (see Discussion). Of the Huaorani studied by other researchers (Larrick et al 1985), 2% have been reported to be KM1 positive, compared with 61% of the Cayapa (P < 0.0001, )~2 = 35.8).…”
Section: Resultssupporting
confidence: 63%
“…One individual was GM 1,17 13, a common phenotype of the Mongoloid race. The distribution of KM allotypes was similar to other South American Indian tribes (Salzano et al , 1991; J. P. Pandey and E L. Black, unpublished observations), with the exception of Huaorani (see Discussion). Of the Huaorani studied by other researchers (Larrick et al 1985), 2% have been reported to be KM1 positive, compared with 61% of the Cayapa (P < 0.0001, )~2 = 35.8).…”
Section: Resultssupporting
confidence: 63%
“…At that time Brazil had about five million inhabitants; . Recently, genetic studies of extant Brazilian Indians have been performed at the protein (Salzano and Callegari-Jacques, 1988;Salzano et al, 1991;Callegari-Jacques et al, 1994Cavalli-Sforza et al, 1994;Salzano et al, 1997), nuclear DNA (Guerreiro et al, 1992;Petzl-Erler and McDevitt, 1994;Bevilaqua et al, 1995;Heidrich et al, 1995;Pena et al, 1995;Santos et al, 1996;Zago et al, 1996;, and mitochondrial DNA Santos et al, 1996;Ward et al, 1996;Bonatto and Salzano, 1997) levels. The first Africans were introduced in Brazil about three decades after the arrival of European colonizers, and during the Colonial slave trade period about six million of them were forced to migrate to this country .…”
mentioning
confidence: 99%
“…The Urubu-Kaapor and Parakan~ speak languages of the same stock and are closer geographically to each other than to the PacMs Novos, who speak a very distinct language. These relationships, however, were not reflected in the genetic distances separating these populations, as calculated using 60 alleles of 20 genetic systems; Pacafis Novos--Urubu-Kaapor, 0.20; Pacafis Novos --Parakan~, 0.49; Parakan~--Urubu-Kaapor, 0.55 (Salzano et al, 1990). In the ORM1 system the Urubu-Kaapor are more similar to the Paca~s Novos than to the Parakan~, while for AHSG the Urubu-Kaapor occupy an almost equidistant position in relation to the other two tribes.…”
Section: Discussionmentioning
confidence: 91%